GAMBARAN CARA MENYIKAT GIGI DENGAN KEJADIAN KARIES GIGI PADA ANAK TK IT INSAN UTAMA ISLAMIC KIDS CENTER 2 PEKANBARU - silvia nova nova; Khairun Nisa (STIKes Al-Insyirah Pekanbaru, 2019)
Caries teeth are infections originating from bacteria which cause demineralization of hard tissues (enamel, dentine and cementum). Caries teeth are also known as damage or cavities in the teeth. Based on WHO year data, 2013 found 60-90% of Kindergartens (TK) in Indonesia have a high risk of caries. The trigger for caries is the high consumption of carbohydrates. The initial survey was carried out by researchers at IT InsanUtama 2 TK Pekanbaru on March 6, 2018, out of 7 children interviewed there were 5 carious children due to not brushing their teeth properly according to health procedures. Type of quantitative descriptive research, samples used total sampling with a study population of 32 children. From the results of the study it can be seen that there are as many as 18 (56.2%) children experiencing dental caries. The results of the study concluded that concern about how to brush teeth properly is still lacking. It is expected that parents can guide or familiarize children with the right way on brushing teeth, which is the right way, right tools, on time and on target.